Evolution of Russian legislation about limited companies in the modern period of development society - Snezhana Ivanovna Sapko (Вестник Северо-Кавказского федерального университета, 2022)
The transition to a market economy and the reform of the legal system in Russia has fundamentally changed the relationship in the regulation of commercial organizations. However, the case law relating to the activities of legal entities, indicating the need to improve civil law of their legal status. This is especially significant improvement of the legislation on limited companies, which are the most common legal form of business organizations.